Automated knowledge visualization and assessment - Pirnay-Dummer, P.; Ifenthaler, Dirk (2010)
In this chapter we introduce a computer-based and highly automated measurement technique which enables us to analyze even large sets of data within a few seconds. Closely linked to the demand of new approaches for designing and developing up-to-date learning environments is the necessity of enhancing the design and delivery of assessment systems and automated computer-based diagnostics. In many settings, manual and therefore labor-intensive methods have limits. Hence, following a general assessment framework design, we introduce several automated and integrated tools which have helped us in many studies so far. The technologies which we discuss in this chapter aim at the assessment, re-representation, analysis, and comparison of knowledge. The tools were developed independently and then integrated step by step. The possible applications go beyond the structural and semantic analysis and comparison of knowledge. The tools also allow the development of self-assessment technologies which can be used directly by the learners. © 2010 Springer-Verlag US.